2015
DOI: 10.1111/eve.12387
|View full text |Cite
|
Sign up to set email alerts
|

Equine odontoclastic tooth resorption and hypercementosis affecting all cheek teeth in two horses: Clinical and histopathological findings

Abstract: Summary This report describes the clinical presentation and histopathological findings of two horses with equine odontoclastic tooth resorption and hypercementosis (EOTRH) affecting all cheek teeth. Equine odontoclastic tooth resorption and hypercementosis is a well documented condition known to affect the incisors, canines and occasionally the premolars in horses. At this time there have been no documented cases of EORTH affecting all cheek teeth described in the peer reviewed literature. This paper documents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 20 publications
0
42
0
4
Order By: Relevance
“…Two very recent studies have shown that EOTRH is not exclusively affecting the incisor and canine teeth [7,29]. Equine canine teeth cannot always be fully evaluated using the standard radiographs for incisor teeth, because of their caudal position and long intra-alveolar part, especially in younger horses with a longer intra-alveolar aspect of these teeth and ponies with short interalveolar margins and small mouths.…”
Section: Discussionmentioning
confidence: 99%
“…Two very recent studies have shown that EOTRH is not exclusively affecting the incisor and canine teeth [7,29]. Equine canine teeth cannot always be fully evaluated using the standard radiographs for incisor teeth, because of their caudal position and long intra-alveolar part, especially in younger horses with a longer intra-alveolar aspect of these teeth and ponies with short interalveolar margins and small mouths.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the accompanying paper hypothesise that the underlying cause of EOTRH may be due to the masticatory forces placed on the geriatric tooth of shorter root length (Schrock et al 2013;Moore et al 2016). This would be similar to the root resorption noted in people undergoing orthodontic treatment.…”
mentioning
confidence: 92%
“…; Moore et al . ). This would be similar to the root resorption noted in people undergoing orthodontic treatment.…”
mentioning
confidence: 97%
See 2 more Smart Citations